We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website.
Please click on "Accept cookies" if you agree to the setting of cookies. Cookies that do not require consent remain unaffected by this, see
cookie policy and privacy policy.
DECLINE COOKIES

Mia has a certain amount of money. If she buys 4 pens and 1 pencil, she will have $5 left over. If she buys 2 pens and 2 pencils, she will have $3 left over. If Edward arrives with the same amount of money as Mia, together they can buy 7 pens and 4 pencils and spend all their money. If \(a\) is the cost of one pen and \(b \) is the cost of one pencil, compute the ordered pair \((a,b) \).

Guest Sep 9, 2018

edited by
Guest
Sep 9, 2018

#1**0 **

Note: This is a long and detailed answer!

Let the amount of money that Mia has =M=same amount of money as Edward has

M - [4a + b] =5

M - [2a + 2b]=3

[7a + 4b] =2M

Solve the following system:

{-4 a - b + M = 5 | (equation 1)

-2 a - 2 b + M = 3 | (equation 2)

7 a + 4 b = 2 M | (equation 3)

Express the system in standard form:

{-(4 a) - b + M = 5 | (equation 1)

-(2 a) - 2 b + M = 3 | (equation 2)

7 a + 4 b - 2 M = 0 | (equation 3)

Swap equation 1 with equation 3:

{7 a + 4 b - 2 M = 0 | (equation 1)

-(2 a) - 2 b + M = 3 | (equation 2)

-(4 a) - b + M = 5 | (equation 3)

Add 2/7 × (equation 1) to equation 2:

{7 a + 4 b - 2 M = 0 | (equation 1)

0 a - (6 b)/7 + (3 M)/7 = 3 | (equation 2)

-(4 a) - b + M = 5 | (equation 3)

Multiply equation 2 by 7/3:

{7 a + 4 b - 2 M = 0 | (equation 1)

0 a - 2 b + M = 7 | (equation 2)

-(4 a) - b + M = 5 | (equation 3)

Add 4/7 × (equation 1) to equation 3:

{7 a + 4 b - 2 M = 0 | (equation 1)

0 a - 2 b + M = 7 | (equation 2)

0 a+(9 b)/7 - M/7 = 5 | (equation 3)

Multiply equation 3 by 7:

{7 a + 4 b - 2 M = 0 | (equation 1)

0 a - 2 b + M = 7 | (equation 2)

0 a+9 b - M = 35 | (equation 3)

Swap equation 2 with equation 3:

{7 a + 4 b - 2 M = 0 | (equation 1)

0 a+9 b - M = 35 | (equation 2)

0 a - 2 b + M = 7 | (equation 3)

Add 2/9 × (equation 2) to equation 3:

{7 a + 4 b - 2 M = 0 | (equation 1)

0 a+9 b - M = 35 | (equation 2)

0 a+0 b+(7 M)/9 = 133/9 | (equation 3)

Multiply equation 3 by 9/7:

{7 a + 4 b - 2 M = 0 | (equation 1)

0 a+9 b - M = 35 | (equation 2)

0 a+0 b+M = 19 | (equation 3)

Add equation 3 to equation 2:

{7 a + 4 b - 2 M = 0 | (equation 1)

0 a+9 b+0 M = 54 | (equation 2)

0 a+0 b+M = 19 | (equation 3)

Divide equation 2 by 9:

{7 a + 4 b - 2 M = 0 | (equation 1)

0 a+b+0 M = 6 | (equation 2)

0 a+0 b+M = 19 | (equation 3)

Subtract 4 × (equation 2) from equation 1:

{7 a + 0 b - 2 M = -24 | (equation 1)

0 a+b+0 M = 6 | (equation 2)

0 a+0 b+M = 19 | (equation 3)

Add 2 × (equation 3) to equation 1:

{7 a+0 b+0 M = 14 | (equation 1)

0 a+b+0 M = 6 | (equation 2)

0 a+0 b+M = 19 | (equation 3)

Divide equation 1 by 7:

{a+0 b+0 M = 2 | (equation 1)

0 a+b+0 M = 6 | (equation 2)

0 a+0 b+M = 19 | (equation 3)

**a = $2, b=$6, M=$19**

Guest Sep 9, 2018

#2**0 **

M - [4a + b] =5.............(1)

M - [2a + 2b]=3...........(2)

[7a + 4b] =2M.............(3)

M=5 + 4a + b -rearrange(1).....................(4)

M=3 + 2a + 2b -rearrange(2) and subt.....(5)

0 =2 + 2a - b.............................................(6)

2M=0 + 7a + 4b - rearrange (3)

2M=10 + 8a + 2b - Multiply (4) by 2 and subt.

0 =-10 - a + 2b.........................................(7)

Solve (6) and (7) as 2 simult.equations.

**a=$2 and b=$6. Sub these into (1) M =$19**

Guest Sep 10, 2018